Community Assessment: A Current Essential Need - Mohammad Hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2014)
Health; as a basic right of the people and essential demand; should be considered as a joint responsibility of the government and people of a community. As much as the people of a community aware and involved in the individual health promotion and problem solving of their community in all dimensions, the probability of reaching to favorable health measurements is also increased. Community assessment is considered as a foundation for health improving and promoting the community members. The main objectives of community assessment are; to identify factors that affect the health of a population and determine the availability of resources within the community to adequately address these factors. In this Vera, community leaders, public health agencies, businesses, hospitals, private practitioners, and academic centers have each one a defined role. These groups can begin to answer key questions such as (a) "What are the strengths in our community?" (b) "What health concerns do community members have?" and (c) "What resources are available and what do we need in the community to address these concerns? An important use of a community health assessment is to create Community Health Action to develop effective community health strategies. The health reform plan of Islamic Republic of Iran, started at the earlier months of the current year (2014), with establishing of the family physician program begun firstly at the level of rural regions, then will developed to cities with population 20000 to 500000 also borderlines of metropolitans cities and finally in the future, covering all urban eras of cities in the country aimed to executive the referral system with all its attributes. Being a full time physician along with a comprehensive teamwork including different prestigious health workers prepare a gold opportunity for implementation of community assessment in these regions. Although, some efforts have been accomplished in some parts of country by academic centers especially School of Public Health, Tehran University of Medical Sciences, under supervision and leadership of Professor Dr. Kourosh Holakouie- Naieni which appreciate these efforts. There is also an essential need in which all academic members in Universities of Medical Sciences of the country involve their students in this line, investment for the future.